Erratum. - Steffen Schmidt; Anna Gerasimova; Fyodor A Kondrashov; Ivan A Adzhubei; Alexey S Kondrashov; Shamil Sunyaev (PLoS Genetics, 2008)
This corrects the article on p. e1000281 in Vol. 4, PMID: 19043566. Hypermutable Non-Synonymous Sites Are Under Stronger Negative Selection.